Grinding performance of micro-texured grinding wheel on different ceramic materials - Yanling LIAO; Fenglin ZHANG; Kaijiang LI; Shanghua WU (Jin'gangshi yu moliao moju gongcheng, 2022)
The grinding performance of micro-textured grinding wheel with arrayed micro-hole and common grinding wheel are compared through experiments on alumina, aluminum nitride, zirconia and silicon nitride ceramic materials. The grinding force, the specific grinding energy, the surface roughness and the surface chipping are analyzed. In comparison with common grinding wheel, micro-textured grinding wheel improves the grinding force and the specific grinding energy in grinding of alumina, aluminum nitride and zirconia ceramics, reduces the surface roughness of these ceramics, but has a little effect on the grinding force and the surface roughness of silicon nitride ceramics. Silicon nitride has higher grinding force and specific grinding energy than other ceramic materials do. The surface characteristics of alumina and aluminum nitride mainly imply brittle removal mode, while a ductile removal mode is characterized on the surface of zirconia and silicon nitride has both plastic and brittle removal characteristics. The surface chipping thickness processed by the micro-textured grinding wheel is larger than that of the common grinding wheel, while the surface chipping thickness of both alumina and aluminum nitride ceramics is larger than those of zirconia and silicon nitride ceramics.